2015
DOI: 10.1021/am508905t
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Surface Engineering for Efficient Printing of Highly Conductive Metal Nanoparticle Inks

Abstract: An approach to polymer surface modification using self-assembled layers (SALs) of functional alkoxysilanes has been developed in order to improve the printability of silver nanoparticle inks and enhance adhesion between the metal conducting layer and the flexible polymer substrate. The SALs have been fully characterized by AFM, XPS, and WCA, and the resulting printability, adhesion, and electrical conductivity of the screen-printed metal contacts have been estimated by cross-cut tape test and 4-point probe mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…In addition to improving the adhesion, the SAMs also help in achieving highly smooth gold films [21]. Earlier reports on vapour-and liquid-phase deposition of MPTMS monolayer involved a process time that was a few hours to 1 week long [18][19][20][21][22][23][24][25][26]. For practical applications, one needs to have faster deposition methods that help the adhesion of gold to substrates as well as smooth, uniformly covered few monolayer gold films.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improving the adhesion, the SAMs also help in achieving highly smooth gold films [21]. Earlier reports on vapour-and liquid-phase deposition of MPTMS monolayer involved a process time that was a few hours to 1 week long [18][19][20][21][22][23][24][25][26]. For practical applications, one needs to have faster deposition methods that help the adhesion of gold to substrates as well as smooth, uniformly covered few monolayer gold films.…”
Section: Introductionmentioning
confidence: 99%
“…By using the hot chromic acid-sulfuric acid cleaning of plastic surface followed by activation with tin chloride and palladium chloride solutions, the conventional plating processes for metallization of polymer are commonly expensive and toxic [20,21]. Therefore, many latest studies [22][23][24][25] have been reported to develop low-cost and environmentally friendly methods for improvement of adhesion between metal coating and the substrate. For example, adhesion strength between metal conductive layer and a polymer was enhanced by sintering above a precise temperature, due to the interfacial fusion between metal film and the underlying polymer [26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, adhesion strength between metal conductive layer and a polymer was enhanced by sintering above a precise temperature, due to the interfacial fusion between metal film and the underlying polymer [26]. Besides, flexible polymer substrates can be applied for oxygen-plasma treatment followed by self-assembling functional alkoxysilanes to form self-assembled layers (SAL), thus improving the interface adhesion [25]. However, many of the suggested methods have several disadvantages, including physical anchoring interface with limited adhesion, complicated equipment and long process time.…”
Section: Introductionmentioning
confidence: 99%
“…3-Mercaptopropyltrimethoxysilane and 3-mercaptopropyl(dimethoxy) methylsilane were obtained from TCI Europe and used as received. 3-Mercaptopropyl(methoxy)dimethylsilane was prepared by a slight modification of a reported procedure [27].…”
Section: Methodsmentioning
confidence: 99%